Implementasi Sistem Informasi Zis Berbasis Web Untuk Transparansi Di Masjid Al-Ikhlas Bandung - Rahman, Atep Aulia; Purnama, Adi; Indriani; Prasetyo, Bagus Alit; Fauzi, Esa; Kusramdani, Rizky; Candimadam; Tumaruk, Andry Septian Syahputra (STMIK Royal, 2025)
Abstract: This community service activity aims to improve the transparency and efficiency of zakat, infaq, and shadaqah (ZIS) management at Al-Ikhlas Mosque, Bandung Regency, through the implementation of a web-based information system. The main problem faced by the partner was the manual and unstructured recording and reporting process, as well as the low accessibility of information for congregants. The methods used included consultation to identify needs, science and technology substitution to implement modern systems, and technical training for mosque administrators. The results showed that the administrators were able to operate the system independently, with a level of understanding reaching 93.5% with an average evaluation score of 3.74 out of 4. The developed information system supports transaction recording, financial reporting, and transparent ZIS fund distribution. Additionally, the activity produced outputs in the form of a web application, digital training modules, and technical documentation that can be used sustainably. This program contributes significantly to strengthening accountability and congregational engagement in religious social fund management. Keywords: accountability; information system; training; web application; zakat Abstrak: Kegiatan pengabdian ini bertujuan untuk meningkatkan transparansi dan efisiensi pengelolaan zakat, infaq, dan shadaqah (ZIS) di Masjid Al-Ikhlas Kab. Bandung melalui implementasi sistem informasi berbasis website. Masalah utama yang dihadapi mitra adalah proses pencatatan dan pelaporan manual yang tidak terstruktur serta rendahnya akses informasi bagi jamaah. Metode yang digunakan meliputi konsultasi untuk identifikasi kebutuhan, substitusi ipteks untuk penerapan teknologi, serta pelatihan teknis untuk pengurus masjid. Hasil kegiatan menunjukkan bahwa pengurus masjid mampu mengoperasikan sistem secara mandiri dengan tingkat pemahaman mencapai 93.5% dengan skor rata-rata evaluasi sebesar 3.74 dari 4. Sistem informasi yang dikembangkan mendukung pencatatan transaksi, pelaporan keuangan, serta transparansi distribusi dana ZIS. Selain itu, kegiatan ini menghasilkan luaran berupa aplikasi web, modul pelatihan digital, dan dokumentasi teknis yang dapat digunakan secara berkelanjutan. Kegiatan ini memberikan kontribusi nyata dalam memperkuat akuntabilitas dan keterlibatan jamaah dalam pengelolaan dana sosial keagamaan. Kata kunci: akuntabilitas; aplikasi web; pelatihan; sistem informasi; zakat